Influence of Cadmium(II) Ions and Brewery Sludge on Metallothionein Level in Earthworms (Eisenia fetida) - Bio- transforming of Toxic Wastes - Huska, Dalibor; Krizkova, Sona; Beklova, Miroslava; Havel, Ladislav; Zehnalek, Josef; Diopan, Vaclav; Adam, Vojtech; Zeman, Ladislav; Babula, Petr; Kizek, Rene (Sensors (Basel, Switzerland), 2008)
Metallothioneins belong to a group of intracellular, high molecular andcysteine-rich proteins whose content in an organism increase with increasing concentrationof a heavy metal. The aim of this work was to apply the electrochemical analysis for theanalysis of metallothioneins in earthworms exposed to cadmium ions and brewery sludge.Here we utilized adsorptive transfer technique coupled with differential pulse voltammetryBrdicka reaction to determine metallothionein in different biological samples. By meansthis very sensitive technique it was possible to analyze metallothionein in concentrationsbelow 1 μmol.l⁻1 with the standard deviation of 4-5%. We found out that the average MTlevel in the non-treated earthworms oscillated between 19 and 48 μmol.l-1. When weanalysed samples of earthworms treated by cadmium, we observed that the MT contentincreased with the exposition length and increase dose of cadmium ions. Finally, weattempted to study and compare the toxicity of the raw sludge and its leach by using ofearthworms. The raw brewery sludge caused the death of the earthworms quickly.Earthworms held in the presence of leach from brewery sludge increased their weight of147 % of their original weight because they ingested the nutrients from the sludge. Themetallothionein level changes markedly with increasing time of exposition and applieddose of toxic compound. It clearly follows from the obtained results that the MT synthesisis insufficient in the first hours of the exposition and increases after more than 24 h.
Keywords: Electrochemistry; Cadmium; Metallothionein; Biochemical marker; Earthworm; Heavy metals; Voltammetry